Nasopharyngeal carriage of Haemophilus influenzae among adults with co-morbidities. Issue 5 (31st January 2022) - Giufrè, Maria; Dorrucci, Maria; Lo Presti, Alessandra; Farchi, Francesca; Cardines, Rita; Camilli, Romina; Pimentel de Araujo, Fernanda; Mancini, Fabiola; Ciervo, Alessandra; Corongiu, Maria; Pantosti, Annalisa; Cerquetti, Marina; et al.
Highlights: Haemophilus influenzae is a commensal of the human nasopharynx. Colonization of the upper respiratory tract can be a reservoir for transmission. H. influenzae colonization prevalence was 10.5% in adults aged ≥50 years. Acute respiratory symptoms were associated with H. influenzae colonization. Colonizing H. influenzae often belong to the same STs of invasive disease isolates. Abstract: After the widespread use of Haemophilus influenzae type b (Hib) vaccine, H. influenzae invasive disease is now commonly due to non-encapsulated (NTHi), affecting mostly the youngest and the elderly. The objective of this study was to investigate H. influenzae nasopharyngeal carriage rate in adults with co-morbidities and possible associated risk factors. Methods: Patients aged >50 years with co-morbidities attending medical centres were examined. A nasopharyngeal swab was analysed for H. influenzae presence by cultural and molecular methods (RT-PCR). Univariable and multivariable analysis of risk factors for H. influenzae carriage were performed. Serotype of isolates was determined by PCR capsular genotyping. Minimum inhibitory concentration (MIC) was determined by MIC gradient test and β-lactamase production was detected by the nitrocephin test. Genotyping was performed by Multilocus sequence typing (MLST). Phylogenetic relationships among carriage and invasive NTHi strains were assessed. Results: Among 248 enrolled patients (median age: 73 years), the carriage rate was 5.6% and 10.5% by cultural method or RT-PCR, respectively. Colonization with H. influenzae was significantly associated with the presence of acute respiratory symptoms (adjusted OR = 12.16, 95% CI: 3.05–48.58, p < 0.001). All colonizing isolates were NTHi. Three isolates (3/14, 21.4%) were resistant to ampicillin and beta-lactamase positive. MLST revealed a high degree of genetic diversity, with 11 different STs from 14 isolates. Eight out of the 11 (72.7%) STs were shared among carriage and invasive isolates. Conclusions: Adults ≥50 years old with co-morbidities are occasionally colonized by H. influenzae, even if the presence of co-morbidities is not a risk factor for colonization. The presence of acute respiratory symptoms is the only factor associated with H. influenzae colonization. Colonizing H. influenzae are all NTHi. Colonizing H. influenzae often belong to the same STs of invasive disease isolates.